O lugar de Pedra Bonita e Cangaceiros na produção literária brasileira : um retrato do sertão nordestino na produção do ciclo do cangaço de José Lins do Rego - Silva, Edvânio Caetano da (2021)
The proposal of the thesis in focus includes an analysis of the books Pedra Bonita, (1938) and Cangaceiros (1953), by José Lins do Rego (1901-1957), in which both novels, through their regionalist, sociological and historical traits, used in literature, build, through narrative fiction, a conception of the northeastern hinterland. Thus, the study also aims to demonstrate how the author appropriates the literary text to make narratives that go beyond the fictional barrier to become, within its limits, also historical and sociological documents about a part of Brazil. This type of analysis is possible since the referenced books expose a physical, psychological and sociological image of the Brazilian northeastern hinterland, based on the social element, through the types of characters, places and spaces that permeate throughout the novels. From this perspective, we intend to carry out an investigation in which author and work are apprehended as distinct elements in the narrative, despite the evident relationship between them. Finally, it should be noted that the two books in question are part of the so-called “cangaço cycle”, in the work of José Lins de Rego, in which the author clashes with the other, the “sugar cane” – with works such as Menino de Engenho (1932), Banguê (1934), Fogo Morto (1943), a cycle that questioned the way of life in the coastal region, aimed at plantation owners -, to weave a narrative with representative characters from the hinterland region, loaded with human drama characteristic of that space. Thus, the work consists of reframing both books considering the criticism of the 1930 novel, among others pertinent to this type of research, in addition to understanding them as belonging to the aesthetic project of José Lins do Rego, thus referenced, their importance to our literature.